Dentifrício fluoretado suplementado com hexametafosfato de sódio sobre o processo de desmineralização do esmalte: estudos in vitro e in situ - Camara, Danielle Mendes da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the ability of conventional dentifrices (1100 ppm F) supplemented with sodium hexametaphosphate (HMP), in reducing enamel demineralization in vitro and in situ. In the study of demineralization of bovine enamel blocks (n = 60) selected by the initial surface hardness (SHI) were divided into five groups of dentifrices (n = 12) without fluoride and HMP without (Placebo); conventional dentifrice 1100 ppm F (1100F); 1100 ppm F associated 0.5% of HMP (1100FHMP0.5%), 1100 ppm F associated 1% of HMP (1100FHMP1%) and 1100 ppm F associated 2% of HMP (1100FHMP2%). The blocks were subjected to pH cycling for five days, and then treatment performed with the respective dentifrices 2x / day. Next, we determined final surface hardness (SHf), surface hardness loss (% SH), integrated differential hardness (ΔIH) and integrated loss of subsurface hardness (ΔKHN) and fluoride (F) in the enamel. The results were submitted to one-way ANOVA followed by the Student-Newman-Keuls test (p <0.001). The group 1100FHMP1% had the lowest mineral loss (SH%, ΔKHN and ΔIH) followed in 1100FHMP0.5% (p <0.001). 1100FHMP1% group had the same concentration of 1100 ppm F in group F. For the study of enamel in situ bovine enamel blocks (n = 144) were selected for the surface hardness and divided into three groups: Placebo (placebo), 1100 ppm F (1100F), 1100 ppm F associated 1% of HMP (1100FHMP1%). Twelve volunteers wore palatal appliances with four enamel blocks for seven days, and brushing performed 3x / day with the palatal device within the oral cavity and the cariogenic challenge with sucrose 30% at pre-established times. After 7 days, SH% was determined, ΔKHN and fluoride (F), calcium (Ca) and phosphorus (P) in enamel. The biofilms formed were analyzed for the concentration of F, Ca, P and extracellular polysaccharide (EPS)...

O objetivo deste estudo foi avaliar a capacidade de dentifrícios convencionais (1100 ppm F) suplementados com hexametafosfato de sódio (HMP), em reduzir a desmineralização do esmalte in vitro e in situ. No estudo in vitro blocos de esmalte bovino (n = 60) selecionados pela dureza de superfície inicial (SHi) foram divididos em cinco grupos de dentifrícios (n = 12): sem fluoreto e sem HMP (Placebo); um convencional de 1100 ppm F (1100F); 1100 ppm F associado 0.5% de HMP (1100FHMP0.5%), 1100 ppm F associado a 1% de HMP (1100FHMP1%) e 1100 ppm F associado a 2% HMP (1100FHMP2%). Os blocos foram submetidos a ciclagem de pH durante cinco dias, sendo o tratamento com os respectivos dentifrícios realizados 2x/dia. A seguir, determinou-se a dureza de superfície final (SHf) e a perda de dureza de superfície (%SH), perda da dureza integrada de subsuperfície (ΔKHN), a dureza diferencial integrada (ΔIH) e fluoreto (F) no esmalte. Os resultados foram submetidos à análise de variância seguida pelo teste Student-Newman-Keuls (p < 0,001). O grupo 1100FHMP1% apresentou a menor perda mineral (%SH, ΔKHN e ΔIH) seguido pelo grupo 1100FHMP0.5% (p < 0,001). O grupo 1100FHMP1% apresentou a mesma concentração de F no esmalte do grupo 1100. Para o estudo in situ, blocos de esmalte bovinos (n = 144) foram selecionados pela dureza de superfície e divididos em três grupos experimentais: Placebo (placebo), 1100 ppm F (1100F), 1100 ppm F associado a 1% de HMP (1100FHMP1%). Doze voluntários utilizaram dispositivos palatinos, com quatro blocos de esmalte, durante sete dias para cada fase, sendo a escovação realizada 3x/dia com o dispositivo palatino no interior da cavidade bucal e o desafio cariogênico com sacarose 30% em horários pré-estabelecidos. Após o período de 7 dias determinou-se %SH, ΔKHN e os níveis de fluoreto (F), cálcio (Ca) e fósforo (P) no esmalte...
Keywords: Esmalte dentário; Flúor; Fosfatos; Desmineralização do dente; Remineralização dentária; Cárie dentária; Dentifrícios; Caries Dental